A Critical Study of Matthew 18:15-18 in New Testament Greek and Selected Akan Mother-Tongue Translations: Implication for Peace-Making in Ghana - Asamoah, Emmanuel Foster; Kpalam, Ebenezer Tetteh (European Scientific Journal, ESJ, 2023)
Current research suggests that the globe is growing more fractured, less peaceful, and riskier for future generations. The world has seen family, marriage, community, and national conflicts in recent years. Ghana has ethnic conflict in many areas despite its low sub-regional conflict score. In a country where over 70% of the population is Christian, contextualising the sacred text to provide a biblical peace approach is crucial. The study examined Matthew 18:15–18 exegetically to inform Ghanaian peace-making initiatives. The study proposes that Ghanaian Christians’ peace-making efforts could benefit from Jesus Christ’s teachings in Matthew 18:15-18 interpreted in the Akan mothers’ vernacular.